The Increase of Social Media-Based Home Business During Pandemic - Trufi Murdiani; Adi Prasetyo; Vistania Jasica (Proceeding International Conference on Information Technology and Business, 2020)
Business is one sector that affected by Covid 19 pandemic. The Micro, Small, and Medium Enterprises (MSME) actors have to find a strategy to keep the business runs well during and after the pandemic. Increasing the selling program by using social media is one effort since the pandemic requires people to do social distancing, stay at home, and facing the swift of lifestyle to use a digital tool. This study dealt with an observation on how the business sector especially in micro, small and medium enterprises improve its products or services promotion and marketing communication amid the decrease of people consumption during pandemic quarantine and new normal eras into digital usage. The methodology of this study used a descriptive qualitative approach by analyzing various literature on digital marketing. The result of this study found that social media had been used actively as a marketing tool by home business during the pandemic and makes many conventional home businesses changed to be a social media-based home business.Keywords:Digital Marketing, Communication, Information, Consumers.